Hematopoietic Stem Cell Niche During Homeostasis, Malignancy, and Bone Marrow Transplantation - Man, Yan; Yao, Xiangmei; Yang, Tonghua; Wang, Yajie (Frontiers in Cell and Developmental Biology, 2021)
Self-renewal and multidirectional differentiation of hematopoietic stem cells (HSCs) are strictly regulated by numerous cellular components and cytokines in the bone marrow (BM) microenvironment. Several cell types that regulate HSC niche have been identified, including both non-hematopoietic cells and HSC-derived cells. Specific changes in the niche composition can result in hematological malignancies. Furthermore, processes such as homing, proliferation, and differentiation of HSCs are strongly controlled by the BM niche and have been reported to be related to the success of hematopoietic stem cell transplantation (HSCT). Single-cell sequencing and in vivo imaging are powerful techniques to study BM microenvironment in hematological malignancies and after HSCT. In this review, we discuss how different components of the BM niche, particularly non-hematopoietic and hematopoietic cells, regulate normal hematopoiesis, and changes in the BM niche in leukemia and after HSCT. We believe that this comprehensive review will provide clues for further research on improving HSCT efficiency and exploring potential therapeutic targets for leukemia.